Religion in America since 1945 : a history - Allitt, Patrick (Columbia histories of modern American life., 2003)
Identifying the major trends and telling moments within both major denominations and other less formal religious movements, Allitt asks how these religious groups have shaped, and been shaped by, some of the most important and divisive political issues and events of the last half century, including the Cold War, the Civil Rights Movement, the Vietnam War, feminism and the sexual revolution, abortion rights, and the antinuclear and environmentalist movements.